Role of ulipristal acetate in management of uterine fibroid - Khan, Farha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Uterine fibroids are most common benign tumors in women of reproductive age group. Prevalence in rural population in India is 37.65% and 24% in urban population. Management depends on number, size, location of fibroid, patients age and fertility preservation. Ulipristal acetate is an orally active synthetic selective progesterone receptor modulator (SPRM). It competes at the progesterone binding site in a tissue specific manner. It decreases fibroid size and relieves symptoms. It inhibits cell proliferation and induces apoptosis leading to shrinkage of tumor. It is indicated for pre-operative treatment and for those who wish to preserve fertility. It is given as four intermittent courses of 5 mg once daily for 3 months. Liver function test has to be done prior to each course. Hence, ulipristal acetate is a promising non-surgical treatment alternative for women with symptomatic uterine fibroids, particularly for those who are not candidates for surgery or who prefer a less invasive approach.